Indonesian public diplomacy on education in Vietnam - Lusianti; Azizah, Nur (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2024)
Based on BPS RI records in 2022, the number of Vietnamese visiting Indonesia have increased but still relatively low at 68,067 people. Therefore, public diplomacy is needed by Indonesia for the Vietnamese. Public diplomacy can be carried out from various fields, to fulfill the national interests of a country. This research will explain the public diplomacy conducted by Indonesia in Vietnam. This research was written using a qualitative method with data derived from previous journals, articles, social media, data from the Indonesian Consulate General in HCMC, and interviews that the author conducted with scholarship awardees from the Indonesian government, lecturers and students from the Indonesian Studies Program USSH VNU HCMC, and lecturers and students from BIPA HCMCOU. As a result, it is found that the form of public diplomacy carried out by Indonesia is in the form of scholarships from the Indonesian government for Vietnamese, Indonesian Study Program USSH VNU HCMC, and BIPA HCMCOU. The Indonesian Consulate General in HCMC has contributed to public diplomacy on education and successfully enhance Indonesia's positive image in Ho Chi Minh City.